2022
DOI: 10.1007/s10147-022-02257-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of risk factors for venous thromboembolism and validation of the Khorana score in patients with advanced lung cancer: based on the multicenter, prospective Rising-VTE/NEJ037 study data

Abstract: Background Management of cancer-associated venous thromboembolism (VTE) is essential in cancer treatment selection and prognosis. However, currently, no method exists for assessing VTE risk associated with advanced lung cancer. Therefore, we assessed VTE risk, including driver gene mutation, in advanced lung cancer and performed a Khorana score validation. Methods The Rising-VTE/NEJ037 study was a multicenter prospective observational study that included p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In a recent multicenter prospective observational study in Japan, the KRS was evaluated in 1008 patients with advanced lung cancer, of whom 10% developed CAT. VTE risk could not be determined because both the Khorana score and modified Khorana score, based on BMI targets adjusted for the Asian population, showed very low areas under the curve (0.518 and 0.516, respectively) [69]. This result was replicated in a large systematic review and meta-analysis of 55 cohorts, where the KRS was of limited use for predicting future risk of CAT in LC patients [66].…”
Section: Risk Assessment Models (Rams) For Cancer-associated Thrombosismentioning
confidence: 99%
“…In a recent multicenter prospective observational study in Japan, the KRS was evaluated in 1008 patients with advanced lung cancer, of whom 10% developed CAT. VTE risk could not be determined because both the Khorana score and modified Khorana score, based on BMI targets adjusted for the Asian population, showed very low areas under the curve (0.518 and 0.516, respectively) [69]. This result was replicated in a large systematic review and meta-analysis of 55 cohorts, where the KRS was of limited use for predicting future risk of CAT in LC patients [66].…”
Section: Risk Assessment Models (Rams) For Cancer-associated Thrombosismentioning
confidence: 99%
“… 17 18 Whether such scoring systems can be applied to East Asian patients is questionable, and it is essential to establish suitable scoring methods for East Asian patients. Although previous studies have demonstrated the prediction of VTE in East Asian individuals, 19 20 21 22 23 these studies used relatively small cohorts and included only specific cancer sites.…”
Section: Introductionmentioning
confidence: 99%